Use of a synthetic biosensor for neutralizing activity-biased selection of monoclonal antibodies against atroxlysin-I, an hemorrhagic metalloproteinase from Bothrops atrox snake venom. - Francisco Santos Schneider; Dung Le Nguyen; Karen Larissa Castro; Sandra Cobo; Ricardo Andrez Machado de Avila; Nivia de Assis Ferreira; Eladio Flores Sanchez; Christophe Nguyen; Claude Granier; Pascale Galéa; Carlos Chávez-Olortegui; Franck Molina (PLoS Neglected Tropical Diseases)
Background The snake Bothrops atrox is responsible for the majority of envenomings in the northern region of South America. Severe local effects, including hemorrhage, which are mainly caused by snake venom metalloproteinases (SVMPs), are not fully neutralized by conventional serum therapy. Little is known about the immunochemistry of the P-I SVMPs since few monoclonal antibodies (mAbs) against these molecules have been obtained. In addition, producing toxin-neutralizing mAbs remains very challenging. Methodology/principal findings Here, we report on the set-up of a functional screening based on a synthetic peptide used as a biosensor to select neutralizing mAbs against SVMPs and the successful production of neutralizing mAbs against Atroxlysin-I (Atr-I), a P-I SVMP from B. atrox. Hybridomas producing supernatants with inhibitory effect against the proteolytic activity of Atr-I towards the FRET peptide Abz-LVEALYQ-EDDnp were selected. Six IgG1 Mabs were obtained (named mAbatr1 to mAbatr6) and also two IgM. mAbatrs1, 2, 3 and 6 were purified. All showed a high specific reactivity, recognizing only Atr-I and B. atrox venom in ELISA and a high affinity, showing equilibrium constants in the nM range for Atr-I. These mAbatrs were not able to bind to Atr-I overlapping peptides, suggesting that they recognize conformational epitopes. Conclusions/significance For the first time a functional screening based on a synthetic biosensor was successfully used for the selection of neutralizing mAbs against SVMPs.